Three hundred and ten million, seven hundred and sixty three thousand, one hundred and thirty six.
Answer:
(2)
Step-by-step explanation:
Let f(x) = y → f-¹(x) = f(y) = x, f(y) is the inverse of f(x)
Thus,
=> -x³ - 9 = y
=> - y - 9 = x³
=> (-y - 9)^(1/3) = x
=> f(y) = x
Inverse is (-y-9)^(1/3)
Replacing the variable, inverse is (-x-9)^(1/3)
Option (2)
Answer:3.8
Step-by-step explanation:
Step-by-step explanation:
emily: 10(5/8) = 6 1/4 or 6.25 pounds left
10- 6.25 = 3.75 used
Frances : 10(2/5) = 4 pounds left
10-4 = 6 pounds used
Bills : 10(2/5) = 4 pounds left
10-4 = 6 pounds used
add them together
15.75 or 15 3/4 pounds of soil in the first flower bed
Into 3 significant figures=4210